Les langages des diables et des âmes perdues des incrédules. Un cas de possession collective dans la République de Venise au XVIIIe siècle - Federico Barbierato (Etudes Epistémè)
In the 1730s, a group of villages in the Venetian Dolomites was the stage of a case of collective possession. Dozens of people, especially women, began to manifest the classic symptoms of demonic possession. Meanwhile, many other people and their animals fell ill and died, according to doctors, because of evil spells and sorcery. The local parish priest, who had already begun to exorcise his parishioners, was instructed by the Venetian government to conduct an inquiry. In the end, he compiled a dossier in which he described the behaviour of the victims of possession, identified those responsible for what was happening, and reported the words of the demons. Two types of language emerge from this dossier : on the one hand, that of the bodies of the possessed men and women, a language composed of actions, movements, repulsions, and emotional manifestations, and on the other hand, the language of the demons, whose words were articulated through the bodies of the possessed and, above all, through the pen of the parish priest. But most importantly, however, the observant language of a proponent of the Roman Church emerges, who did not neglect the opportunity to argue against growing religious scepticism, which was becoming increasingly widespread in both the intellectual and popular spheres.